Penerapan Teknik Cognitive Restructuring untuk Mereduksi Perilaku People Pleaser (Studi Kasus pada Klien “A” di Sentra Budi Perkasa Palembang) : Penelitian - Novi Ramayani; Neni Noviza; Lena Marianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the people pleaser behavior of Client "A" at the Budi Perkasa Center, Palembang and analyze the application of Cognitive Restructuring techniques to reduce this behavior. People pleaser behavior in client "A" is characterized by difficulty in making decisions, a thirst for judgment and recognition from others, frequent apologies for unnecessary things, and a tendency to neglect personal needs to please others. This qualitative study uses a case study method. Data collection techniques involve observation, interviews, and documentation. Data analysis uses pattern matching techniques, data explanation, and time series analysis. The results of the study show a clear picture of Client "A's people pleaser behavior, which is reinforced by the presence of cognitive distortions in the form of underlying irrational thought patterns. The application of Cognitive Restructuring techniques through individual counseling is carried out to help clients recognize these distortions, change irrational thought patterns, and form more realistic and healthy ways of thinking. The intervention results showed that this technique was able to help client "A" reduce people-pleasing tendencies, improve her ability to set personal boundaries, and build a more positive self-concept.